2017
DOI: 10.1007/s10597-017-0124-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Therapeutic Fly-Fishing Program for Veterans with Combat-Related Disabilities: A Community-Based Rehabilitation Initiative

Abstract: The purpose of this study was to examine the outcomes of a therapeutic fly-fishing program for veterans with combat-related disabilities. A total of 40 veterans participated in the 4-day therapeutic fly-fishing program and this study. The outcomes examined included reducing symptoms of posttraumatic stress (PTS), depression, perceived stress, functional impairment (i.e., work, relationships, physical, and everyday life), increasing self-determination, and leisure satisfaction. Each research participant complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…In recent years researchers have begun to explore the possibility that outdoor recreational activity experiences may have therapeutic benefit to military veterans with PTSD. Outdoor recreational experiences have attracted a multitude of labels including 'green exercise' [23,28], 'therapeutic recreation' [29], 'forest bathing' [30] 'peer outdoor support therapy' [31], 'nature adventure rehabilitation' [32], 'nature based therapy' [33] and 'nature recreation experience' [34]. These interventions often combine the benefits of a natural environment with learning a new recreational skill from certified professionals.…”
Section: An Alternative Approach: Outdoor Recreation Experiencesmentioning
confidence: 99%
“…In recent years researchers have begun to explore the possibility that outdoor recreational activity experiences may have therapeutic benefit to military veterans with PTSD. Outdoor recreational experiences have attracted a multitude of labels including 'green exercise' [23,28], 'therapeutic recreation' [29], 'forest bathing' [30] 'peer outdoor support therapy' [31], 'nature adventure rehabilitation' [32], 'nature based therapy' [33] and 'nature recreation experience' [34]. These interventions often combine the benefits of a natural environment with learning a new recreational skill from certified professionals.…”
Section: An Alternative Approach: Outdoor Recreation Experiencesmentioning
confidence: 99%
“…It is imperative to examine whether Veterans have disproportionate access to green space and nature, given evidence that green space and nature settings have the potential to improve psychological well-being, social functioning, and life outlook. [32][33][34]…”
Section: Resultsmentioning
confidence: 99%
“…The study suggested nature as a co-therapist and an effective method for decreasing symptoms of PTSD and contributing to rehabilitation. Similarly, Bennett et al 34 found signifi cant mental health benefits associated with a "fl y-fi shing" intervention program for Veterans with PTSD. Th rough focus group discussions, the latter study provided an increased understanding of how Veterans perceive therapeutic outdoor-based recreation programs and the associated mental health benefi ts.…”
Section: Interventions and Restoration Effects Related To Green Spacementioning
confidence: 94%
See 1 more Smart Citation
“… 12 For unique populations such as veterans with combat-related disabilities or patients with breast cancer, fly-fishing has been shown to increase subjective and objective measures of healing and quality of life. 1 , 6 , 7…”
mentioning
confidence: 99%